1971
DOI: 10.1039/c29710000939
|View full text |Cite
|
Sign up to set email alerts
|

Nonclassical oxidation of cymenes

Abstract: Sunz~nary Cobalt (111) ion-catalysed co-oxidation of pcymene and butane affords predominantly p-isopropylbenzoic acid, contrary to the prediction based on the classic a1 free-radical mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In fact, most oxidation systems, except at very low conversions, ought to be treated as co-oxidation systems because of the participation of the products. Deliberate co-oxidation routes have also been attempted for the oxidation of p -xylene to terephthalic acid by using butane, , acetaldehyde, and paraldehyde 8 as co-oxidizing substances. However, the commercial success of such a process also depends on the market for the coproduct.…”
Section: Historical Developmentmentioning
confidence: 99%
“…In fact, most oxidation systems, except at very low conversions, ought to be treated as co-oxidation systems because of the participation of the products. Deliberate co-oxidation routes have also been attempted for the oxidation of p -xylene to terephthalic acid by using butane, , acetaldehyde, and paraldehyde 8 as co-oxidizing substances. However, the commercial success of such a process also depends on the market for the coproduct.…”
Section: Historical Developmentmentioning
confidence: 99%
“…Isostearic acids are important commercially successful products used in many applications including body washes , coatings , cosmetics , lubricant additives , hydraulic fluids , and emulsifiers . Our group found that zeolites such as Ferrierite can catalyze the skeletal isomerization of ulc‐FAs to give a high selectivity of branched‐chain fatty acids and conversion .…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, we studied the carbonylation of 1-octadecene, a C18 internal olefin mixture, 1-eicosene, and a commercial C20-24 -olefin fraction (Onopchenko and Schulz, 1974). The effect of the reaction conditions on the formation of Ci9 Koch acid yields is shown in Figures 2 and 3.…”
Section: Resultsmentioning
confidence: 99%